Diseño de un plan de negocios para la comercialización de banano deshidratado como alternativa de desarrollo para la cooperativa Cobaoro - Vega González, Laura Luzmila (2014)
This business plan is intended to find an alternative development for members of the association COBAORO , due to which the market study was conducted , the same resulting in that 89.72 % of respondents indicated willingness to buy and consume the product. The product will be named " cobito " which is a short name, easy to pronounce and striking, the introductory price will be 40 cents covers 31 grams , the distribution is made from the plant to the dealers to these may make people hit the stores and then to the final consumer. A marketing plan with radio advertising, written (local media ) and print (posters, etc.) designed to publicize the benefits of the product. Within the technical study found that production capacity is 193,548 cases per month 31 grams. The financial and economic study indicated that fixed investment including working capital amounts to 537 US $ 418.97 and the flow of expenditure was estimated at $ 246 312.14 per annum. Also it was found that the flow of annual sales revenue is $ 518 979.24 The project will be implemented with the support of 60% equity and 40% funded, which gives an IRR of 44.21 % and a NPV of $ 515 347,00 . It was established that the equilibrium in monetary units is $ 149 710.11 ie 28.85% of the total revenue and units is 374,275 FUNDIT 31 grams. The payback period on investment is 5 years, 6 months and 4 days. In the optimistic scenario analysis indicates that if demand increases by 10 % , the price by 5% and costs have decreased 5% NPV would increase to US $ 863 782,00 was considered. In the pessimistic scenario was raised that if demand fell by 40 %, the price would drop by 10 % and costs were increased by 10% resulting NPV would be $ 9 486,00 ; in either of these scenarios the project would be feasible since shareholders would recover the investment and obtain profit.